How Did Canada’s Increasing Lentil Production Affect Turkey? Is There A Possible Win-Win Situation for Both Countries? - Cevher Özden (Turkish Journal of Agriculture: Food Science and Technology)
Competition is fierce in the world markets of agricultural products. It is especially harder for developing countries to compete with the wealthier industrialized countries. Canada entered in the lentil production mainly for export purposes in the early 1990s and exports nearly all of its lentil products every year. As Canada has become the dominant power in lentil trade, Turkey’s lentil production has declined notably. In the study, Turkey’s adaptation to this trend is investigated. Based on the results, it is concluded that Turkey’s market share has not changed in its traditional markets and its export has risen both in quantity and value. For instance, Turkey’s lentil export has increased from 127 Thousand tons in 1997 to 178 Thousand in 2013. This is achieved through partnerships between Canadian and Turkish entrepreneurs. Furthermore, lentil producers in Turkey have shifted to alternative crops, which yields higher income.